11-Keto-α-Boswellic Acid, a Novel Triterpenoid from Boswellia spp. with Chemotaxonomic Potential and Antitumor Activity against Triple-Negative Breast Cancer Cells - Michael Schmiech; Judith Ulrich; Sophia Johanna Lang; Berthold Büchele; Christian Paetz; Alexis St-Gelais; Tatiana Syrovets; Thomas Simmet (Molecules, 2021)
Boswellic acids, and particularly 11-keto-boswellic acids, triterpenoids derived from the genus Boswellia (Burseraceae), are known for their anti-inflammatory and potential antitumor efficacy. Although boswellic acids generally occur as α-isomers (oleanane type) and β-isomers (ursane type), 11-keto-boswellic acid (KBA) was found only as the β-isomer, β-KBA. Here, the existence and natural occurrence of the respective α-isomer, 11-keto-α-boswellic acid (α-KBA), is demonstrated for the first time. Initially, α-KBA was synthesized and characterized by high-resolution mass spectrometry (HR-MS) and nuclear magnetic resonance (NMR) spectroscopy, and a highly selective, sensitive, and accurate high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) method was developed by Design of Experiments (DoE) using a pentafluorophenyl stationary phase. This method allowed the selective quantification of individual 11-keto-boswellic acids and provided evidence for α-KBA in Boswellia spp. oleogum resins. The contents of α-KBA as well as further boswellic acids and the composition of essential oils were used to chemotaxonomically classify 41 Boswellia oleogum resins from 9 different species. Moreover, α-KBA exhibited cytotoxicity against three treatment-resistant triple-negative breast cancer (TNBC) cell lines in vitro and also induced apoptosis in MDA-MB-231 xenografts in vivo. The respective β-isomer and the acetylated form demonstrate higher cytotoxic efficacies against TNBC cells. This provides further insights into the structure-activity relationship of boswellic acids and could support future developments of potential anti-inflammatory and antitumor drugs.